Correlation between Pro-Environmental Behavior and Environmental Values of Female Pre-Service Science Teachers in Indonesia - N. F. Sulaeman; A. Nuryadin; S. Dinurrohmah; L. Subagiyo; E. Andrianto (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
In contrast with the global trend of male domination in science and technology, Indonesia’s pre-service science teacher program is widely attracted to female students. This study aims to investigate the correlations between pre-service science teachers’ pro-environmental behaviors (PEB) and values toward the environment through one-time cross-sectional survey studies. Information was collected from a sample of the predetermined population at one point, followed by correlational studies designed to explore the correlations between the variables under study. The questionnaire consists of three aspects of PEB (preservation, utilization, and appreciation) and four aspects of value (biospheric, altruistic, egoistic, and hedonic). A total of 273 female pre-service science teachers enrolling in four public universities in Indonesia participated through an online questionnaire. The purposive sampling method was chosen to constitute the sample of this study. In order to analyze the data collected, descriptive statistics and correlation tests were utilized. According to the results, it can be concluded that pre-service science teachers held good environmental behaviors and values. The aspects of preservation and appreciation have a positive correlation, while utilization is negative. The four aspects of value are all at high levels, as is their correlation. This result indicates that female pre-service science teachers have positive behavior and value toward the environment. Moreover, the pre-service science teacher program should encourage understanding and behavior toward the environment to prepare future science lessons more aligned with the environment.